Unbiasedness Hypothesis and Efficiency Test of Thai Stock Index Futures - Piyapas Tharavanij (2018)
© 2017, © The Author(s) 2017. Theoretically, futures prices are unbiased predictors of subsequent cash prices only if a market is efficient and there is no risk premium. This research empirically tests both market efficiency hypothesis and unbiasedness of futures price hypothesis in the context of Thai stock index futures (SET50 futures). This article also investigates whether any long-run or short-run inefficiencies or pricing biases exist by identifying and estimating a risk premium. This article finds that in the long run, futures and subsequent cash prices move together and are cointegrated with one cointegrating vector. The statistical test could not reject the null hypothesis of futures unbiasedness. The results do not support the existence of a constant risk premium. The error terms are also free from autocorrelation as required by market efficiency. In the short run, this research could not detect a constant or a time-varying risk premium. This result does not support either normal backwardation hypothesis (futures price < average subsequent cash price) or contango hypothesis (futures price > average subsequent cash price). The overall results support the unbiasedness hypothesis.